Small business finance in Finland: A descriptive study - Ari Hyytinen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2002)
Using new data originating from a recently conducted survey, this paper examines the financing of small and medium-sized enterprises (SMEs) in private equity and debt markets in Finland. We find that the three most important sources of funds are the principal owner's equity, trade credit provided by non-financial firms and debt provided by financial institutions (FIs). These account for about 2/3 of total debt and equity. The Finnish SMEs run a debt ratio of 54%, but it is lower for small than for large SMEs. The debt ratio also varies non-monotonically with the age of firms. Overall, the capital structure of the Finnish SMEs does not seem to fundamentally differ from that in the US (when the study of Berger and Udell (1998) is used as the US benchmark). There are however some evidence that as the Finnish SMEs age, they increase indebtness slowly compared to the US SMEs. The young SMEs also utilize less FI debt in Finland than in the US. We also find that the financing of innovative and R&D-intensive SMEs differs in several aspects from that of other SMEs. The data shows that innovative firms, firms with R&Dactivities and firms that own patents and/or intangible assets run a lower debt ratio than their counterparts. The difference is most notable for the most R&D-intensive SMEs, which also rely less on debt supplied by FIs than other firms do. SMEs with R&Dactivities seem to resort more on inside equity than other SMEs do. The analysis suggests that a partially “reversed” pecking order may best characterize innovation finance. We also provide new evidence on main sources, concentration and interconnectedness of innovation finance. – – Tutkimuksessa analysoidaan suomalaisten pienten ja keskisuurten (pk) yritysten rahoituksen lähteitä uuteen kyselyaineistoon perustuen. Kolmen tärkeimmän rahoituslähteen, pääomistajan osakesijoituksen, kauppaluottojen ja rahoituslaitosluottojen, osuus koko rahoituksesta on noin 2/3. Pk-yritysten velkasuhde on 54% ja se on korkeampi suurilla kuin pienillä pk-yrityksillä. Velkasuhde vaihtelee epälineaarisesti yrityksen iän mukaan. Näyttää siltä, että suomalaisten pk-yritysten pääomarakennetta koskevat tulokset eivät poikkea merkittävästi yhdysvaltalaisista tuloksista. Joitain viitteitä on kuitenkin siitä, että pk-yritysten velkasuhde kasvaa iän myötä hitaammin Suomessa kuin Yhdysvalloissa ja että Suomessa nuorilla yrityksillä rahoituslaitosluottojen osuus on pienempi. Innovatiivisten, T&K-intensiivisten ja aineettomia oikeuksia omistavien pk-yritysten velkasuhde on alhaisempi verrattuna muihin pk-yrityksiin. Ero on huomattavin kaikkein T&K-intensiivisimpien yritysten kohdalla, joilla on lisäksi suhteellisesti vähemmän rahoituslaitosluottoja kuin muilla yrityksillä. T&K:ta harjoittavat yritykset näyttäisivät turvatuvan suhteellisesti vähemmän ulkopuoliseen osakerahoitukseen kuin muut pkyritykset. Tutkimuksen valossa osittain käänteinen rahoituslähteiden ”nokkimisjärjestys” voi kuvata parhaiten innovatiivisten pk-yritysten rahoitusta. Tutkimuksessa saadaan lisäksi uusia tuloksia innovatiivisten pk-yritysten päärahoittajista, rahoituksen keskittyneisyydestä ja eri rahoituslähteiden korrelaatiosta. – Yritysrahoitus ; pääomarakenne ; pk-yritys ; T&K ; innovatiivisuus
Keywords: 330; Corporate finance; capital structure; SME; R&D; innovativeness; Unternehmensfinanzierung; Klein- und Mittelunternehmen; Kapitalstruktur; Statistischer Test; Finnland